Digital Literacy Analysis on Online Learning Outcomes for Macroeconomics with Gender-Mediated and Family Socio-economics as Moderating Variables - Estu Niana Syamiya; Sri Lestari; Debi Wulandari; Dian Ekawati (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This study aims to analyze whether digital literacy simultaneously and significantly affects academic learning outcomes mediated by gender in students, whether digital literacy simultaneously and significantly affects academic learning outcomes moderated by the socio-economic family of students, and whether digital literacy simultaneously and significantly affects academic learning outcomes mediated by gender and family socio-economics as a moderator for macroeconomics students. By using a quantitative method with the Conditional Process Analysis process using the SPSS Macro Process, the instrument used is saturated sample is a census, where all members of the population are sampled. the population in this study amounted to 272 from Mahaputra Muhammad Yamin University, STKIP Cokroaminoto Pinrang, Mataram University and Sheikh Yusuf Islamic University. The result is int_1 has a P value of 0.5379 where the value is greater than a significance value of 0.05. This means that there is no moderating effect of socio-economics on the relationship between digital literacy and learning outcomes, the P-value = 0.0467 less than 0.05, meaning that line a (digital literacy variable to gender) here states that there is a gender effect (male/gender). female) in mastering digital literacy and the P value of 0.5146 is greater than 0.05. This means that there is no mediating effect of gender and socio-economic moderators on digital literacy on learning outcomes. has implications for students in improving their soft skills, hard skills and also improving learning outcomes by providing facilities.